Nuclear magnetic resonance studies of ribonucleic acids. Issue 2 (2003) - Ohlenschläger Ohlenschläger, Oliver Oliver; Wöhnert Wöhnert, Jens Jens; Ramachandran Ramachandran, Ramadurai Ramadurai; Sich Sich, Christian Christian; Görlach Görlach, Matthias Matthias
Abstract : Ribonucleic acids (RNA) and RNA−protein complexes are essential components of biological information transfer, catalytic processes and are associated with regulatory functions. This broad range of biological functions is paralleled at the conformational level by a large number of non-canonical structural elements or sequences with non-standard backbone conformations, e.g., loops, bulges, pseudo-knots and complex tertiary folds. NMR spectroscopy has evolved to a powerful tool for the determination of ribonucleic acid structures of up to 20 kDa. Uniform or selective stable isotope labelling aids in solving assignment problems arising from the inherently limited chemical shift dispersion and overlap of resonances for larger nucleotide sequences. Recent developments of multi-dimensional heteronuclear NMR pulse sequences allow e.g., to directly observe the hydrogen bonding pattern of canonical Watson−Crick base pairs as well as of unusual types of base pairs, thereby opening up a fast access to secondary structure screening of RNA. Detailed conformational descriptions are obtained using conventional NOE and J coupling-derived data, nowadays supplemented by information from residual dipolar couplings. The latter method also provides a new means for the probing of dynamical features of ribonucleic acids.